OPTIMASI PENJADWALAN PENGIRIMAN PRODUK JADI MENGGUNAKAN PENDEKATAN BINARY INTEGER PROGRAMMING (Studi Kasus di PT Tiga Pilar Sejahtera Surakarta) - Sriyanto, Sriyanto; Susanti, Estie (J@ti Undip : Jurnal Teknik Industri, 2006)
Scheduling is still a cumbersome activity for an industry with complex orders. As does PT Tiga Pilar Sejahtera (TPS),  a growing national company which produces noodles, TPS management also have trouble in planning their order delivery schedule. Intuition still on the first place to pursue their policy. Intuition in decision making itself, is based on the experience of the decision maker. Without an enough the use of intuition only  in dealing with delivery scheduling can result in a costly delivery schedule. Optimize the delivery schedule means that a manager should decide the optimal way in delivering orders. Its means the right time and the right choice of how an order should be delivered. The probability of  consolidating orders must be considered. Consolidation in TPS is done for two reasons, which are, to minimize total transportation cost and to minimize the risk of product damage along its trip to their destination points.  Binary integer programming with its ability to model yes or no decision, has proved that it can effectively solve this delivery scheduling problem. By modeling this problem in to BIP form, deciding  the right way in delivering orders were no longer became one difficult thing to do.   Keywords : delivery schedule, consolidation, Binary Integer Programming